Protein hydrolysates of niosome-encapsulated skipjack (Katsuwonus pelamis) viscera: Antioxidant, anticancer, and release properties - Shima Kaveh; Alireza Sadeghi Mahoonak; Vahid Erfani-Moghadam; Mohammad Ghorbani; Aliakbar Gholamhosseinpour; Mojtaba Raeisi (Applied Food Research)
Skipjack (Katsuwonus pelamis) is one of the main tuna fish varieties in the canning industry. Approximately 50% of processed fish, particularly the viscera, which contains valuable compounds, is generated as waste with limited use. Recovering these bioactive compounds is a sustainable approach that can provide an excellent source of high-added value compounds, benefit the economy, and reduce environmental pollution. However, the wide application of these compounds in pharmaceutical and food fields is hindered due to their physical and chemical instability and uncontrolled delivery. So, this study aimed to produce skipjack viscera protein hydrolysates (FPH) using different enzymes (pancreatin, alcalase, trypsin, and pepsin) at different hydrolysis times. Additionally, the study investigated the stabilization of FPH by partially replacing cholesterol with cholecalciferol and squalane in nano-sized niosomes. The FPH produced by pancreatin at 200 min of hydrolysis exhibited the highest antioxidant and anticancer effects. These FPHs were then loaded into niosomes containing different ratios of stabilizers. The niosome formulation containing cholesterol, cholecalciferol, and squalane at a ratio of 2:1:1 achieved favorable encapsulation efficiency (91.8%) and retained total antioxidant capacity during simulated gastrointestinal fluids. The niosomes were observed to be spherical with smooth surfaces based on FE-SEM results, and successful loading of FPH in niosomes was confirmed by FTIR. As a result, niosomes containing cholecalciferol and squalane are stable carriers for the controlled release of bioactive drugs, including FPH as a high-added value product.